Pengaruh Good Corporate Governance dan Ukura Perusahaan terhadap Pengungkapan Sustainability Report serta Dampaknya terhadap Return Saham: Studi Empiris pada perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia Periode 2018 – 2020 - Anggun Mita Tri Kusumawardani (Owner : Riset dan Jurnal Akuntansi, 2022)
This research aims to examine the effect of institutional ownership, board of commissioners, audit committee, and firm size on the disclosure of sustainability reports and their effect on stock returns. The data analysis method used is panel data regression analysis using eviews version 10. In this study, the sampling technique used was purposive sampling. The sample of this research is banks that publish financial reports and sustainability reports during 2018, 2019, and 2020 where finally 10 banks are obtained. Statistical method using multiple linear regression analysis, with hypothesis testing statistical test t. The results of this study indicate that the size of the company affects the sustainability report and the disclosure of the sustainability report can mediate the effect of institutional ownership, the board of commissioners, the audit committee, and the size of the company on stock returns. Institutional ownership, the board of commissioners, the audit committee have no effect on the sustainability report. Institutional ownership, board of commissioners, audit committee, company size, and sustainability report have no effect on stock returns.